Knowledge needs in rural tourism in Czech Republic - Dömeová, Ludmila; Zeipelt, Rudolf (Applied Studies in Agribusiness and Commerce, 2011)
Rural tourism has gone through an important development, but in the Czech Republic has only been possible to run a private business only in last 18 years. In Czech Republic that form of tourism is not very widespread, although there is great potential in it and the neighboring countries such as Austria or Germany are on a much higher level. For more intensive development and better competitiveness on the marker a proper education is necessary especially on the secondary level. An inquiry investigation has been provided. The responders were owners and operators of small businesses in rural tourism. The first part of the questionnaire was focused on the matters of ownership, running the business, promotion, internet services, etc. The subsequent part of the questionnaire gathered the information about the capacity of the places, the types and prices of accommodation, and the facilities. It also surveys the surroundings of the place – both natural and cultural sights.The survey has brought interesting facts about the level of the rural tourism of selected regions.The inquiry investigation was made by trained persons who gathered much information above the framework of the questionnaire. Many demands and complains were concerned with lack of specialized education, needs of new study programs and branches. There are many specifics of this branches, the most important is that there are more than 90% of micro firms. If we want to keep the special features of the rural tourism we have to prepare future entrepreneurs and employees in completely different way than those for big hotels, spas or congress centers. The contribution deals with the present status of rural tourism in Czech Republic and the educational need of the people involved.